Premenstrual Syndrome Is Associated With a Higher Frequency of Female Sexual Difficulty and Sexual Distress - İlhan, Gülşah; Verit Atmaca, Fatma Verda; Kurek Eken, Meryem; Akyol, Hürkan (Journal of sex & marital therapy, 2017)
Few prospective studies have evaluated the impact of premenstrual symptoms (PMS) on female sexual function and sexuality-related distress. The purpose of the present study was therefore to find out risk factors of PMS for  female sexual function and sexuality-related personal distress. This prospective cohort study was conducted at the Süleymaniye Women and Children's Health Training and Research Hospital in Istanbul, Turkey, between February 2014 and March 2016. The study group consisted of women admitted to the general gynecology outpatient clinic aged 18 to 40 years who met the inclusion criteria. The American College of Obstetricians and Gynecologists criteria were used for the initial diagnosis of PMS and the participants were allocated to PMS(+) and PMS(−) groups (healthy subjects). All participants completed the Beck Depression Inventory to exclude those at risk for depression. The patients with an initial diagnosis of PMS then completed the PMS Daily Record of Severity of Problems form prospectively for two consecutive menstrual cycles to confirm PMS diagnosis. Lastly, both sexual function and sexual distress of eligible PMS(+) (n = 143) and PMS(−) (n = 143) participants were assessed with both the Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale-Revised (FSDS-R). According to the FSFI cutoff value, 77.6% of patients in the PMS(+) group and 27.3% of patients in the PMS(−) group had sexual concerns (p < 0.05). The sexuality-related personal distress rate was 51.7% in the PMS(+) group and 24.5% in the PMS(−) group (p < 0.05). Overall, 51.7% of the PMS(+) and 24.5% of the PMS(−) group were recognized as having sexual difficulties based on the presence of sexual distress and the low FSFI scores (p < 0.05). We concluded that women with PMS are likely to have sexual difficulties and a higher level of sexual distress, emphasizing the importance of the sexual aspects of PMS in clinical practice.